2021
DOI: 10.1038/s41598-021-92091-5
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic profiling identifies prognosis-related genes in the immune microenvironment of endometrial carcinoma

Abstract: Endometrial carcinoma (EC) is a common malignancy of female genital system which exhibits a unique immune profile. It is a promising strategy to quantify immune patterns of EC for predicting prognosis and therapeutic efficiency. Here, we attempted to identify the possible immune microenvironment-related prognostic markers of EC. We obtained the RNA sequencing and corresponding clinical data of EC from TCGA database. Then, 3 immune scores based on the Estimation of STromal and Immune cells in MAlignant Tumor ti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Accumulating evidence indicates that the expression profile plays an indispensable role in inflammation, immunity, and inhibition of tumour progression 7 , especially in the development and progression of digestive tract tumours 9 , 40 , 41 ; however, there are no related studies on EC. Furthermore, most studies have focused on a single TME cell type or single protease, but the overall TME infiltration characteristics mediated by the combined effects of multiple MMPs have not been comprehensively recognized 4 . In this study, we analysed the clinical information and transcriptome data of EC patients from TCGA, and identified three distinct MMP expression patterns which displayed differences in immune cell infiltration and different disease prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence indicates that the expression profile plays an indispensable role in inflammation, immunity, and inhibition of tumour progression 7 , especially in the development and progression of digestive tract tumours 9 , 40 , 41 ; however, there are no related studies on EC. Furthermore, most studies have focused on a single TME cell type or single protease, but the overall TME infiltration characteristics mediated by the combined effects of multiple MMPs have not been comprehensively recognized 4 . In this study, we analysed the clinical information and transcriptome data of EC patients from TCGA, and identified three distinct MMP expression patterns which displayed differences in immune cell infiltration and different disease prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is a necessity for accurate screening tools to identify early EC patients. Recently, numerous studies have demonstrated a correlation between matrix metalloproteinases (MMPs) and EC 3 , 4 . Therefore, the functional roles and regulatory mechanisms of MMPs in EC need to be further investigated, and it is crucial to elucidate the association between MMPs and prognosis of EC.…”
Section: Introductionmentioning
confidence: 99%
“…Cells like endothelial cells, macrophages, myofibroblasts, and inflammatory cells communicate via cytokines, ligands receptors, and growth factors with EC cells and create a suitable microenvironment for tumor cell invasion and metastasis. The factors of microenvironment-derived signals and stromal cell-derived proteins are potential targets as biomarkers for the detection of metastatic EC ( Cheng et al, 2021 ).…”
Section: Endometrial/uterine Cancer- Tumor Microenvironmentmentioning
confidence: 99%
“…The morbidity and mortality of UCEC has shown an increasing trend worldwide in recent years ( 2 ). Surgery combined with adjuvant therapy (radiotherapy and/or chemotherapy) is the standard treatment for UCEC ( 3 ).…”
Section: Introductionmentioning
confidence: 99%